Persepsi Orangtua tentang Pelaksanaan Manajemen Peserta Didik di SDN 11 Magek Sumatera Barat - Syukra Vadhillah; Hendri Budi Utama (Indonesian Journal of Islamic Educational Management, 2023)
This research was conducted because there were no number of students in first grade in the 2022/2023 academic year at SDN 11 Magek accompanied by rumors that the school would be merged with another elementary school close to the school and would even be closed. These two issues made researchers interested in conducting research. The location of this research was carried out at SDN 11 Magek. Descriptive qualitative is the method used in this research. Data was obtained from open interviews and observations. Interviews were conducted with 5 parents of students, 1 teacher and 2 people from the community who live around the school. Observations were made on the learning process. Data analysis was carried out by reduction, presentation and conclusions and verification. Data validity by triangulating methods and triangulating sources. The research showed that parents' perceptions regarding the implementation of student management at SDN 11 Magek showed that student planning was not carried out optimally, the organization or division of work in terms of assisting students' talents and interests was not good and the assessment of student learning outcomes in terms of grade promotion was carried out without clear rule and procedures